Influence of Deoxynivalenol and Zearalenone in Feed on Animal Health - Gajęcki, Maciej; Gajęcka, Magdalena (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Humans and animals are continuously exposed to different unwanted actions of compounds, including mycotoxins present in food, water, and air. The presence of mycotoxins is a reason for different disease states or tissue and organism dysfunction. New work should facilitate a more accurate description of the degree of species sensitivity and more efficient dietary management, using environmental influences to improve plant material and animal health quality during primary production. On the other hand, better knowledge of the different forms of enzymes participating in mycotoxin biotransformation would enable more efficient preventive and therapeutic actions in many disease states in which the aetiology was not fully understood until now.